2014
DOI: 10.11648/j.ab.20140202.12
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Serum Free Testosterone Level on Glycemic Control and Atherosclerosis in Type 2 Diabetic Men

Abstract: Background: Atherosclerosis is a complex disease of the arteries characterized by endothelial dysfunction, vascular inflammation, and the build-up of lipids within the intima of the vessel wall. Testosterone has a central or permissive role in pathogenesis of the metabolic syndrome and type 2 diabetes. Insulin resistance is associated with several CVD risk factors such as obesity, dyslipidaemia, hypertension and the proinflammatory state. We aim to disclose the relationship between serum testosterone concentra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 39 publications
(40 reference statements)
2
1
0
Order By: Relevance
“…This is in agreement with previously published data. 33 , 48 , 49 In the present study, multivariate logistic regression analysis of the studied variables revealed that HBA1c was not a significant predictor of LST, which is consistent with the results obtained by some studies. 4 , 7 , 48 In addition, as reported before, levels of HBA1c were higher in patients with ED than in those without ED.…”
Section: Discussionsupporting
confidence: 92%
“…This is in agreement with previously published data. 33 , 48 , 49 In the present study, multivariate logistic regression analysis of the studied variables revealed that HBA1c was not a significant predictor of LST, which is consistent with the results obtained by some studies. 4 , 7 , 48 In addition, as reported before, levels of HBA1c were higher in patients with ED than in those without ED.…”
Section: Discussionsupporting
confidence: 92%
“…The presence of low free testosterone levels in our patients suggests that testosterone insufficiency may be a risk factor for type 2 diabetes. This is found to be comparable with other studies [21,22]. Men with diabetes have significantly lower serum concentrations of T-testosterone than no diabetic men.…”
Section: Discussionsupporting
confidence: 92%
“…Similar to our study, Al Hayek et al 15 and Corona et al 16 reported that the prevalence of low testosterone was higher in patients with a longer duration of DM. Also, another study on 123 men with T2 DM by shaheen et al 17 showed a negative correlation between serum testosterone and duration of diabetes. On the other hand Dhindsa et al 1 and Mirzae et al 19 reported no significant correlation between hypogonadism and duration of diabetes.…”
Section: Discussionmentioning
confidence: 92%